Health Education on Ctps in Commemoration World H-CTPS - Mardiana Mardiana; Fahrurrozi Fahrurrozi; Hanifah Tanjung; Refa Yulia Rossanty; Mentari Cahya Ningrum (Global Health Science Group, 2020)
Clean and Healthy Behavior (PHBS) is one of the programs for development in the health sector. School is one of the places for PHBS implementation. There are 8 indicators in PHBS in the school environment, one of which is the habit of Handwashing with Soap (CTPS). CTPS is important to do in everyday life to reduce the risk of health problems such as diarrhea and food poisoning. Health education about CTPS in Elementary School of Integral Al-Hakim Samarinda are important to be carried out as an effort to increase knowledge and awareness to students to be able to familiarize CTPS behavior. The activity uses health education methods for 83 students at Elementary School of Integral Al-Hakim Samarinda. Measuring the increase in knowledge is done through a pretest - posttest and testing the results using a statistical analysis of the Wilcoxon test. Based on the analysis of the Wilcoxon test at α = 0.05, the results of the pretest-posttest health education about CTPS obtained p value of 0,000 < 0,05. This means that there are significant differences in knowledge between students before and after CTPS education at Elementary School of Integral Al-Hakim Samarinda. Health education about CTPS can enhance student knowledge.